Applications of rough sets in big data analysis: An overview - Pięta, Piotr; Szmuc, Tomasz Bartłomiej (1948- ) (Zielona Góra: Uniwersytet Zielonogórski)
Big data, artificial intelligence and the Internet of things (IoT) are still very popular areas in current research and industrial applications. Processing massive amounts of data generated by the IoT and stored in distributed space is not a straightforward task and may cause many problems. During the last few decades, scientists have proposed many interesting approaches to extract information and discover knowledge from data collected in database systems or other sources.
Keywords: rough sets theory; big data analysis; deep learning; data mining; tools